PENEGAKAN NETRALITAS ASN MELALUI PEMBERDAYAAN PADA PEMERINTAH PROVINSI SULAWESI TENGGARA - Lily, Misnawati (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
ASN neutrality violations are an issue that frequently occur and constantly needed to be discussed as it repeatedly happens especially prior to the democratic elections. The handling of this issue is regularly centred on monitoring and taking measures against violators. Despite the fact that ASNs who violate the neutrality do not necessarily constitute ‘perpetrators’, they may also be ‘victims’ who are obligated to follow their leaders’ instructions. The purpose of this research is to describe the ASN neutrality problems in Southeast Sulawesi. The research aims to discover various policies of the Regional Government of Southeast Sulawesi Province and identify the obstacles in implementing those policies. This research was conducted through direct interviews with the Provincial Government of Southeast Sulawesi and literature studies including books, journals, and articles, as well as other data that support this research. This study found that violations of ASN neutrality were quite widespread in Southeast Sulawesi when compared to other regions. Consequently, ASNs must be empowered in order to gain adequate competence and a clear bargaining position. Through an analysis using the empowerment theory, looking at the spreading awareness, promoting capacity building and empowerment efforts, it is known that the Provincial and Regency/City Governments have made tremendous efforts to empower ASNs. However, various obstacles hinder the implementation on the ground, such as limited budgets, unnecessary programs or activities, and inconsistent implementation of the regulations.